Enhanced chondrogenic differentiation of iPS cell-derived mesenchymal stem/stromal cells via neural crest cell induction for hyaline cartilage repair - Zujur, Denise; Al-Akashi, Ziadoon; Nakamura, Anna; Zhao, Chengzhu; Takahashi, Kazuma; Aritomi, Shizuka; Theoputra, William; Kamiya, Daisuke; Nakayama, Koichi; Ikeya, Makoto (Frontiers in Cell and Developmental Biology, 2023)
Background: To date, there is no effective long-lasting treatment for cartilage tissue repair. Primary chondrocytes and mesenchymal stem/stromal cells are the most commonly used cell sources in regenerative medicine. However, both cell types have limitations, such as dedifferentiation, donor morbidity, and limited expansion. Here, we report a stepwise differentiation method to generate matrix-rich cartilage spheroids from induced pluripotent stem cell-derived mesenchymal stem/stromal cells (iMSCs) via the induction of neural crest cells under xeno-free conditions. Methods: The genes and signaling pathways regulating the chondrogenic susceptibility of iMSCs generated under different conditions were studied. Enhanced chondrogenic differentiation was achieved using a combination of growth factors and small-molecule inducers. Results: We demonstrated that the use of a thienoindazole derivative, TD-198946, synergistically improves chondrogenesis in iMSCs. The proposed strategy produced controlled-size spheroids and increased cartilage extracellular matrix production with no signs of dedifferentiation, fibrotic cartilage formation, or hypertrophy in vivo. Conclusions: These findings provide a novel cell source for stem cell-based cartilage repair. Furthermore, since chondrogenic spheroids have the potential to fuse within a few days, they can be used as building blocks for biofabrication of larger cartilage tissues using technologies such as the Kenzan Bioprinting method.